miR-24 and miR-122 Negatively Regulate the Transforming Growth Factor-β/Smad Signaling Pathway in Skeletal Muscle Fibrosis - Yaying Sun; Hui Wang; Yan Li; Shaohua Liu; Jiwu Chen; Hao Ying (Elsevier, 2018)
Fibrosis is common after skeletal muscle injury, undermining tissue regeneration and function. The mechanism underlying skeletal muscle fibrosis remains unveiled. Transforming growth factor-β/Smad signaling pathway is supposed to play a pivotal role. However, how microRNAs interact with transforming growth factor-β/Smad-related muscle fibrosis remains unclear. We showed that microRNA (miR)-24-3p and miR-122-5p declined in skeletal muscle fibrosis, which was a consequence of transforming growth factor-β. Upregulating Smad4 suppressed two microRNAs, whereas inhibiting Smad4 elevated microRNAs. Luciferase reporter assay and chromatin immunoprecipitation confirmed that Smad4 directly inhibited two microRNAs. On the other hand, overexpression of these two miRs retarded fibrotic process. We further identified that Smad2 was a direct target of miR-24-3p, whereas miR-122-5p targeted transforming growth factor-β receptor-II. Both targets were important participants in transforming growth factor-β/Smad signaling. Taken together, a positive feedback loop in transforming growth factor-β/Smad4 signaling pathway in skeletal muscle fibrosis was identified. Transforming growth factor-β/Smad axis could be downregulated by microRNAs. This effect, however, was suppressed by Smad4, the downstream of transforming growth factor-β.